Cognitive control, reward-related decision making and outcomes of late-life depression treated with an antidepressant. Issue 14 (14th July 2015) - Alexopoulos, G. S.; Manning, K.; Kanellopoulos, D.; McGovern, A.; Seirup, J. K.; Banerjee, S.; Gunning, F.
Abstract : Background: Executive processes consist of at least two sets of functions: one concerned with cognitive control and the other with reward-related decision making. Abnormal performance in both sets occurs in late-life depression. This study tested the hypothesis that only abnormal performance in cognitive control tasks predicts poor outcomes of late-life depression treated with escitalopram. Method: We studied older subjects with major depression ( N = 53) and non-depressed subjects ( N = 30). Executive functions were tested with the Iowa Gambling Test (IGT), Stroop Color-Word Test, Tower of London (ToL), and Dementia Rating Scale – Initiation/Perseveration domain (DRS-IP). After a 2-week placebo washout, depressed subjects received escitalopram (target daily dose: 20 mg) for 12 weeks. Results: There were no significant differences between depressed and non-depressed subjects on executive function tests. Hierarchical cluster analysis of depressed subjects identified a Cognitive Control cluster (abnormal Stroop, ToL, DRS-IP), a Reward-Related cluster (IGT), and an Executively Unimpaired cluster. Decline in depression was greater in the Executively Unimpaired ( t = −2.09, df = 331, p = 0.0375) and the Reward-Related ( t = −2.33, df = 331, p = 0.0202) clusters than the Cognitive Control cluster. The Executively Unimpaired cluster ( t = 2.17, df = 331, p = 0.03) and the Reward-Related cluster ( t = 2.03, df = 331, p = 0.0433) had a higher probability of remission than the Cognitive Control cluster. Conclusions: Dysfunction of cognitive control functions, but not reward-related decision making, may influence the decline of symptoms and the probability of remission of late-life depression treated with escitalopram. If replicated, simple to administer cognitive control tests may be used to select depressed older patients at risk for poor outcomes to selective serotonin reuptake inhibitors who may require structured psychotherapy.